The national tax powers and the communitarisation of the rules in the West African region - (:unkn) unknown (My University, 2015)
West African states, after an unsuccessful experience through ECWA, engaged in aprocess of integration in the image of the European Union with the signing of the UEMOATreaty on 1st January 1994. This process, which aims to harmonize tax rules mean thatnow powers of taxation are assigned to Community institutions and challenge the exclusivecompetence of the Member States advocated by national constitutions in the matter.Therefore, to accompany the common monetary policy and the commercial, UEMOA hasstrived to frame the fiscal powers of the Member States through legislation in the tax area,sometimes bordering the powers of States, now fully taking these powers. After twentyyears of experience, the study's objective is to take stock of integration in West Africa,highlighting the strengths and weaknesses.
Keywords: African Research